Species selectivity for charcoal production in three ecological zones of Nigeria (2012)
Several factors influence the quantity of charcoal production in different parts of Nigeria. The study investigated species selectivity for charcoal production in three ecological zones of Nigeria. Data were obtained through the use of structured interview schedule administered to three hundred and twenty seven respondents selected through snowball. The data were subjected to descriptive and analysis of variance. The results show that the mean age of respondents was 44, male (88.1%), primary school leaving certificate (42.2%), married (92.0%), respondents with charcoal production as primary occupation is 41.0%. Mean for years of experience was 13 years and income mean from charcoal per annum was ₦217,336.4. Respondents made use of earth mound method to produce charcoal. Major source of trees for charcoal production is natural vegetation. Mean for number of trees spp. used is 10.6, charcoal yield of trees spp. (mean =7.6), availability of trees spp. (mean =13.2), and emerging trees spp. (mean=7.1). Charcoal is produced in both dry and wet season with average of 16,000kgs/annum. Analysis of variance inferred that there are significant differences between source of trees for charcoal production (F= 3.951), number of trees spp. used (F=173.824), charcoal yield of trees spp. (F=238.062), availability of trees spp. (F= 47.413) and emerging trees spp. (F=208.192). More foresters/environmental extension agents should be employed and equipped to monitor the activities of rural dwellers in the forest. Forest licensing and fees collection must be restructured, re-orgarnised and increased to prevent illegal logging.